Unannounced vs announced in situ simulation of emergency teams: Feasibility and staff perception of stress and learning. Issue 5 (15th January 2019) - Freund, Debra; Andersen, Peter O.; Svane, Christian; Meyhoff, Christian S.; Sørensen, Jette L.
Abstract : Background: Simulation‐based medical education, often used for teaching teamwork, can be conducted in different settings: off‐site (simulation centers or other settings away from clinical units) or in situ (real clinical environment), where the latter can be either announced or unannounced. Simulation in general, but especially unannounced in situ simulation, has been described as stressful and stress can affect learning. The aim of this study was to evaluate feasibility and the perception of learning and stress. Methods: Sixteen standardized in situ simulations were planned in an emergency department on eight predetermined dates, with one unannounced and one announced simulation per day. Authentic ad hoc teams were formed based on the on‐call staff and included doctors, nurses, radiographers, biochemist, porters, and secretaries. Data were collected using questionnaires and the State‐Trait Anxiety Inventory. Results: Eleven of the 16 in situ simulations were completed. Self‐perceived learning was "good" or "very good" for 27/47 (57%) participants and 33/50 (66%) in unannounced vs announced in situ simulation ( P  = 0.33). Two of 47 (4%) in unannounced in situ simulation "agreed or partly agreed" that in situ simulation was stressful or unpleasant vs 12/50 (24%) in announced in situ simulation ( P  = 0.06). Conclusion: No significant difference was found between unannounced and announced in situ simulation among emergency department staff according to self‐perceived learning and self‐perceived stress. This is relevant for the future planning of simulation when considering what is to be achieved from implementing different designs for simulation‐based medical education.